Army, Navy, Air Force and Research? The Vocation of Scholarship as an Applied Discipline in the Canadian Forces - Catherine Bates (University of Windsor, 2006)
This article is a personal and professional reflection on scholarship and research as applied to a very large and mechanistic organization - the Canadian Forces. A specialist cadre of officers within the Canadian Forces is dedicated to the applied discipline of Training Development. Training Development is the practical application of adult education theory and, in an academic institution, would normally provide ample scope for research. However, the shortage of professional Training Development Officers in the Canadian Forces leaves little time for research given the urgent requirement to train and deploy ever-increasing numbers of Army, Navy and Air Force personnel to theatres of operations abroad. Those officers who practice scholarship through research pursuits often do so to satisfy personal rather than professional goals. The engagement in professional research projects is filled with challenges that include identification of key stakeholders, selection of a topic, and the ethics of rationalizing personal areas of academic interest with military areas of need. The result is a focus on applied rather than academic research. To ethically conduct applied research using Canadian Forces subjects requires the active participation of unrelated departments and the use of both personal and work time to complete the research task. The greatest gains in efficiency can be achieved through position related research. Although there are challenges associated with the pursuit of scholarship in a military setting, there is also ample scope for examination of topic areas not previously addressed through research. The article concludes with recommendations for research into institutional effectiveness, leader experiences and future requirements through a combination of position related and personal interest generated research.